(untitled) (Lex localis - Journal of Local Self-Government, 2025)
Digital transformation can empower enterprises with great new momentum for innovation, but the variety and high cost of digital technologies make it a concern for enterprises to fully leverage digital technologies for corporate innovation. This article explores from the perspective of new public service theory. Based on the data of Shanghai and Shenzhen A-share listed companies in China from 2007 to 2020, a two-way fixed-effects model is used to examine the impact of digital transformation on the sustainable innovation of enterprises and its mechanism of action. The results find that digital transformation effectively promotes the sustainability of corporate innovation inputs and also corporate innovation outputs. Thus, digital transformation significantly contributes to the sustained innovation of firms. The conclusions can provide empirical evidence for a deeper understanding of the linear impact of digital transformation on firms’ continuous innovation, and thus the use of moderating mechanisms to promote continuous innovation.